2021
DOI: 10.1128/msphere.00132-21
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Klebsiella Infections among Hospitalized Patients with Preexisting Colonization

Abstract: Klebsiella is a leading cause of health care-associated infections. Patients who are intestinally colonized with Klebsiella are at a significantly increased risk of subsequent infection, but only a subset of colonized patients progress to disease.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
1
19
0
2
Order By: Relevance
“…Pairwise core gene SNV counts were extracted from the SNV alignment described above, and used to infer transmission networks comprising nodes (one representative isolate per infection episode) connected by edges where the pairwise distance was ≤25 SNVs (based on our previous investigation of within-patient vs between-patient SNV distances 31 , and other recent studies of CP K. pneumoniae transmission 38 , 39 ) and the temporal distance was ≤45 days (twice the median of time-to-infection estimated for colonized patients 14 ). The network function in the R package network (v1.17.1) was used to construct the transmission network, and to extract clusters of connected nodes (isolates).…”
Section: Methodsmentioning
confidence: 99%
“…Pairwise core gene SNV counts were extracted from the SNV alignment described above, and used to infer transmission networks comprising nodes (one representative isolate per infection episode) connected by edges where the pairwise distance was ≤25 SNVs (based on our previous investigation of within-patient vs between-patient SNV distances 31 , and other recent studies of CP K. pneumoniae transmission 38 , 39 ) and the temporal distance was ≤45 days (twice the median of time-to-infection estimated for colonized patients 14 ). The network function in the R package network (v1.17.1) was used to construct the transmission network, and to extract clusters of connected nodes (isolates).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study in which we identified the strong association between the ter operon and infection was limited to patients that developed pneumonia and bacteremia (13). However, Kp is also an important cause of UTI in colonized patients (7, 11). In a previous survey of 2,549 urine associated Kp isolates, we found that 8.4% contained ter (14).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have demonstrated a strong association (odds ratio ~4.0) between gut colonization and infection, indicating that infectious Kp originates from the gut of colonized patients (6)(7)(8)(9). Colonization rates are variable, ranging as high as >75% in hospitalized patients (10), though several large studies indicate a colonization rate closer to 20% (6)(7)(8), depending on seasonal effects (11). Therefore, Kp can successfully and silently tolerate the hostile gut environment before causing disease (12).…”
Section: Introductionmentioning
confidence: 99%
“…(222) Atualmente, a colonização intestinal por ERC tem sido considerada também um fator de risco para o desenvolvimento de infecções. (27,39,222,223) As bases para esta progressão da colonização para a infecção não estão esclarecidas, mas são reportados na literatura alguns fatores de virulência que contribuem para o estabelecimentos de infecções por Klebsiella pneumoniae, dentre eles ICEKp e manBC. (8,152) O sideróforo Ybt é codificado pelos genes fyuA, irp1 e irp2 e o locus Ybt, e juntamente com o T4SS formam as ilhas de patogenicidade denominadas ICE.…”
Section: Discussionunclassified
“…(222) Além da disseminação no ambiente, a colonização intestinal por ERC tem sido considerada um fator de risco para o desenvolvimento de infecções. (22,27,39,222,223) Alguns estudos epidemiológicos demonstraram que pacientes colonizados por ERC, incluindo KpRC e carreadores de blaKPC, desenvolveram infecções por bactérias da mesma espécie, sugerindo ser a mesma cepa em ambos os episódios. (23,224) Baseado nos fatores de risco do paciente, um score de risco foi proposto para tentar prever e evitar que as infecções ocorram em pacientes colonizados por KpRC (Giannella score).…”
Section: Classificação De Patógenos Como Endêmicos E Esporádicosunclassified